Quantitation of 1,4-Dichlorobenzene and Thymol in Beeswax Using Dynamic Headspace Vacuum Transfer in Trap Extraction Prior to Gas Chromatography-Mass Spectrometry - Christina Kast; Marion Fracheboud; Pascal Fuchsmann (Molecules, 2022)
A method based on dynamic headspace vacuum transfer in trap extraction, followed by gas chromatography coupled with a mass spectrometer (DHS-VTT-GC-MS), was validated for the fast quantitation of 1,4-dichlorobenzene (p-dichlorobenzene; PDCB) and thymol residues in beeswax. The quantitation limits (LOQ) were 0.05 mg/kg (PDCB) and 0.25 mg/kg (thymol). Recoveries above 80% were obtained for PDCB concentrations between 0.05 and 10 mg/kg and for thymol concentrations between 0.25 and 200 mg/kg. Analysis of beeswax samples showed a good correlation between the results obtained by DHS-VTT-GC-MS analysis and those of a previous method based on SPE extraction followed by gas chromatography and triple- quadrupole mass spectrometry (GC-MS/MS) (R2 = 0.9770 for PDCB and 0.9666 for thymol). However, the sample preparation and chromatography were much shorter using the DHS-VTT-GC-MS method. Forty comb foundations samples produced in Switzerland in 2019 and 2021 were analysed using DHS-VTT-GC-MS. Fourteen samples contained PDCB above the LOQ of 0.05 mg/kg, ranging up to a maximum of 1.53 mg/kg. The mean concentration of the positive samples was 0.22 mg/kg. All samples contained thymol residues ranging between 3.9 and 84.4 mg/kg with mean and median concentrations of 22.7 mg/kg and 17.4 mg/kg. Residue levels of PCDB and thymol in Swiss beeswax were substantially below those measured 20 (PDCB) and 10 (thymol) years ago, respectively.